Citizens’ Initiative to Cope with The Environmental Problem in Samarinda, Indonesia - Andi Wahyudi; Kemal Hidayah (Indonesian Association for Public Administration, 2022)
This paper aims to examine the citizens’ initiative (CI) to save the Karang Mumus River in Samarinda, Indonesia, through a collective movement, namely GMSS SKM (Gerakan Memungut Sehelai Sampah Sungai Karang Mumus). The river has complicated problems that are mostly caused by human behavior, such as pollution and illegal dwelling. Drawing on the CLEAR (Can do, Like to, Enabled to, Ask to, and Responded to) framework, this research explores the effort of the movement to what extent it engages to save the river. Data in this research are collected at least in two ways, such as interviews and field observation. This research finds out that the local government seems powerless to tackle the river’s problems, therefore the voluntary movement emerges and takes some of the roles. The activists or volunteers use their own resources to run their activities (Can do). They set at least four programs to educate people and the impact will save the environment in the city (Like to). The movement is open for all citizens and communities to join in their activities (Enabled to). They mobilize the group members and publish their activities on social media to attract other citizens (Ask to). It works when some citizens and communities are willing to participate in the activities. The local government then supported the voluntary group by creating a small team of Hantu Banyu. However, some local government officials and local parliament members support the voluntary group individually rather than institutionally. On the other hand, institutional support comes from the central government agency in the city. Moreover, some support also comes from individuals, communities, and the private sector (Responded to).